Continental degassing of He-4 by surficial discharge of deep groundwater - Aggarwal, Pradeep K.; Matsumoto, Takuya; Sturchio, Neil C.; Chang, Hung K. [UNESP]; Gastmans, Didier [UNESP]; Araguas-Araguas, Luis J.; Jiang, Wei; Lu, Zheng-Tian; Mueller, Peter; Yokochi, Reika; Purtschert, Roland; Torgersen, Thomas (Nature Publishing Group, 2015)
Radiogenic He-4 is produced by the decay of uranium and thorium in the Earths mantle and crust. From here, it is degassed to the atmosphere(1-5) and eventually escapes to space(1,5,6). Assuming that all of the He-4 produced is degassed, about 70% of the total He-4 degassed from Earth comes from the continental crust(2,-5,7). However, the outgoing flux of crustal He-4 has not been directly measured at the Earths surface(2) and the migration pathways are poorly understood(2-4,7,8). Here we present measurements of helium isotopes and the long-lived cosmogenic radio-isotope Kr-81 in the deep, continental-scale Guarani aquifer in Brazil and show that crustal He-4 reaches the atmosphere primarily by the surficial discharge of deep groundwater. We estimate that He-4 in Guarani groundwater discharge accounts for about 20% of the assumed global flux from continental crust, and that other large aquifers may account for about 33%. Old groundwater ages suggest that He-4 in the Guarani aquifer accumulates over half- to one-million-year timescales. We conclude that He-4 degassing from the continents is regulated by groundwater discharge, rather than episodic tectonic events, and suggest that the assumed steady state between crustal production and degassing of He-4, and its resulting atmospheric residence time, should be re-examined.